The central role of DNA damage in immunosenescence - Kell, Loren; Simon, Anna Katharina; Alsaleh, Ghada; Cox, Lynne S. (Frontiers in Aging, 2023)
Ageing is the biggest risk factor for the development of multiple chronic diseases as well as increased infection susceptibility and severity of diseases such as influenza and COVID-19. This increased disease risk is linked to changes in immune function during ageing termed immunosenescence. Age-related loss of immune function, particularly in adaptive responses against pathogens and immunosurveillance against cancer, is accompanied by a paradoxical gain of function of some aspects of immunity such as elevated inflammation and increased incidence of autoimmunity. Of the many factors that contribute to immunosenescence, DNA damage is emerging as a key candidate. In this review, we discuss the evidence supporting the hypothesis that DNA damage may be a central driver of immunosenescence through senescence of both immune cells and cells of non-haematopoietic lineages. We explore why DNA damage accumulates during ageing in a major cell type, T cells, and how this may drive age-related immune dysfunction. We further propose that existing immunosenescence interventions may act, at least in part, by mitigating DNA damage and restoring DNA repair processes (which we term ‘genoprotection’). As such, we propose additional treatments on the basis of their evidence for genoprotection, and further suggest that this approach may provide a viable therapeutic strategy for improving immunity in older people.